The 2011 WPATH Standards of Care and Penile Reconstruction in Female-to-Male Transsexual Individuals - Gennaro Selvaggi; Cecilia Dhejne; Mikael Landen; Anna Elander (Advances in Urology)
The World Professional Association for Transgender Health (WPATH) currently publishes the Standards of Care (SOC), to provide clinical guidelines for health care of transsexual, transgender and gender non-conforming persons in order to maximize health and well-being by revealing gender dysphoria. An updated version (7th version, 2011) of the WPATH SOC is currently available. Differences between the 6th and the 7th versions of the SOC are shown; the SOC relevant to penile reconstruction in female-to-male (FtM) persons are emphasized, and we analyze how the 2011 WPATH SOC is influencing the daily practice of physicians involved in performing a penile reconstruction procedure for these patients. Depending by an individual’s goals and expectations, the most appropriate surgical technique should be performed: the clinic performing penile reconstruction should be able to offer the whole range of techniques, such as: metoidioplasty, pedicle and free flaps phalloplasty procedures. The goals that physicians and health care institutions should achieve in the next years, in order to improve the care of female-to-male persons, consist in: informing in details the individuals applying for penile reconstruction about all the implications; referring specific individuals to centers capable to deliver a particular surgical technique; implementing the surgery with the most updated refinements.